Inversión pública del sector de energía eléctrica y su relación con la producción de electricidad de la Empresa Regional de Servicio Público de Electricidad Oriente S.A. en la región Loreto, periodo 2016 - 2020 - Anaya Matute, Keila Milagros (2023)
According to economic theory, one of the macroeconomic variables that are closely related to the behavior of the aggregate economic activity is the production of electricity, therefore, it is interesting to investigate what factors may be related to the performance of such production. Given this, this thesis seeks to determine the relationship between the public investment of the three levels of government in the electrical energy sector and the production of electricity by the Empresa Regional de Servicio Público de Electricidad Oriente S.A. (Electro Oriente) in the Loreto region; In this way, a linear econometric analysis is proposed that will allow measuring said possible relationship between the aforementioned public investment in electrical energy with the production of electricity. In the study, it is possible to show that if such public investment in electrical energy increases by 1%, it is associated with a statistically significant growth (at a 90% confidence level) of 3% over the electricity production of Electro Oriente in Loretto.